Polarização da jornada e dos rendimentos do trabalho: assimetrias de gênero no Brasil (2012-2019) - Marina Mudesto Marques (2021)
If on the one hand, extended working hours are considered prejudicial for the productivity and well-being of the worker, on the other hand, short involuntary hours are characteristics of low productive jobs, with low incomes and concentration of female labor. In this regard, the main point of this dissertation is to analyze for the urban Brazil during the period of 2012-2019 the movement of polarization regarding the working hours and labor income according to individual characteristics and work positions connected to asymmetries and gender inequalities in the occupational and sectorial structure. The motivation comes from the various transformations of the Brazilian labor scenario that bring impacts on the length of the working hours: it includes the changes in the composition of the workforce – the increase of the women and the elderly participation and decrease of the young; the structural factors – the advance of new technologies, outsourcing and deindustrialization; and the conjectural factors - changes in labor legislation and oscillation in the economic activity, for example. Microdata from Pesquisa Nacional por Amostra de Domicílios Contínua Anual (PNADC) are used for the application of the methodologies: descriptive analysis; multinominal logit models and quantile regressions; and the alternative proposal of the analysis of variations in working hours and income/hour linked to educational – which make it possible to examine in detail how the various arrangements of working hours fall on income asymmetries between genders. The results indicate that, over time, there was an intensification of the chances of being on very short and very long working hours. Polarized working hours and incomes tend to fall disproportionally on the minority groups in the labor market – women, blacks, young people and the less qualified labor force. Monthly and hourly earnings measures differ in terms of their association with working hours: for the first, the longer the average working hours, the higher the earnings return; for the latter, results suggest that workers who work long hours are penalized in their incomes. This is compatible with technological changes that drive the increase of jobs demand on digital platforms, which tends to have longer working hours and lower hourly incomes. In addition, different patterns of working hours are identified among occupational and sectorial groups, reflected in gender wage gaps, especially in higher hierarchical positions.